Peer Review Process in Scholarly Communication and Scientific Publishing - Khatri, Bishnu Bahadur (Nepalese Journal of Development and Rural Studies, 2020)
Peer review in scholarly communication and scientific publishing, in one form or another, has always been regarded as crucial to the reputation and reliability of scientific research. In the growing interest of scholarly research and publication, this paper tries to discuss about peer review process and its different types to communicate the early career researchers and academics.This paper has used the published and unpublished documents for information collection. It reveals that peer review places the reviewer, with the author, at the heart of scientific publishing. It is the system used to assess the quality of scientific research before it is published. Therefore, it concludes that peer review is used to advancing and testing scientific knowledgeas a quality control mechanism forscientists, publishers and the public.